2017
DOI: 10.2135/cropsci2016.10.0866
|View full text |Cite
|
Sign up to set email alerts
|

Maize Yield as a Function of Water Availability across Precipitation Years in the North China Plain

Abstract: Crop water production functions require precise knowledge of crop productivity across a wide range of soil water availability (WA). Field studies have demonstrated the yield response of maize (Zea mays L.) to WA, but the relationship has not been quantified across various precipitation years in the North China Plain (NCP). This study was conducted to investigate the effects of the simulated interannual variability in precipitation on maize yield in a winter wheat (Triticum aestivum L.) –summer maize double‐cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Moreover, the value of HI is highly dependent on the crop species and field management techniques [50,51], but such factors were controlled in the same condition for all lysimeters in our study. According to the mathematical regression results, the maximum values of the grain and biomass yield derived from the Richards function were at a reasonable level (around 6 t ha −1 for the grain yield and around 16 t ha −1 for the biomass), and the calculated yields were in an acceptable range considering the usual degree of variability of the field data [52]. It suggests that the Richard equation could be a practical way to describe the effect of the SIR on both the grain and biomass yield, since there must be an upper limit for yield production no matter how many favorable field measures are adopted.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, the value of HI is highly dependent on the crop species and field management techniques [50,51], but such factors were controlled in the same condition for all lysimeters in our study. According to the mathematical regression results, the maximum values of the grain and biomass yield derived from the Richards function were at a reasonable level (around 6 t ha −1 for the grain yield and around 16 t ha −1 for the biomass), and the calculated yields were in an acceptable range considering the usual degree of variability of the field data [52]. It suggests that the Richard equation could be a practical way to describe the effect of the SIR on both the grain and biomass yield, since there must be an upper limit for yield production no matter how many favorable field measures are adopted.…”
Section: Discussionmentioning
confidence: 88%
“…Maize is also known as one of the highest water-using crops in different regions [3,4]. Thanks to a continent monsoon climate, annual precipitation falls between 400 and 600 mm in the NCP, with 65% of precipitation occurring in maize seasons [5], while annual evapotranspiration ranges from 800 to 900 mm: 50-100% higher than precipitation [6]. For decades, crop water consumption has been being supplemented by extracting the declining groundwater in the NCP at a speed exceeding aquifer recharge [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the equation, ETc stands for water loss from soil surface and plants whereas precipitation and irrigation represents water input. Water-saving strategies largely depend on the monitoring and controlling of ETc [5,6]. There are numerous methods available for estimating ETc [12][13][14][15], among which weighing lysimetry is normally used as a standard means [16].…”
Section: Introductionmentioning
confidence: 99%
“…Regression between ET c and LAI demonstrated that there was no significant correlation between them. Previous studies determined the relationships between E/ET (ratio of soil evaporation to ET c ) and LAI, and some of them concluded a high correlation between them [7,8]. It is no surprising that LAI significantly influenced E/ET as E/ET was closely related to crop canopy coverage.…”
Section: Resultsmentioning
confidence: 99%